Crystal Structure of Biotin Synthase, an S-Adenosylmethionine-Dependent Radical Enzyme - Berkovitch, Frederick (2004)
The crystal structure of biotin synthase from Escherichia coli in complex with S-adenosyl-l-methionine and dethiobiotin has been determined to 3.4 angstrom resolution. This structure addresses how “AdoMet radical” or “radical SAM” enzymes use Fe(4)S(4) clusters and S-adenosyl-l-methionine to generate organic radicals. Biotin synthase catalyzes the radical-mediated insertion of sulfur into dethiobiotin to form biotin. The structure places the substrates between the Fe(4)S(4) cluster, essential for radical generation, and the Fe(2)S(2) cluster, postulated to be the source of sulfur, with both clusters in unprecedented coordination environments.